Noncoding RNAs responsive to nitric oxide and their protein-coding gene targets shed light on root hair formation in Arabidopsis thaliana - Santos, Camilla Alves; Moro, Camila Fernandes; Salgado, Ione; Braga, Márcia Regina; Gaspar, Marília (Frontiers in Genetics, 2022)
An overview of the total Arabidopsis thaliana transcriptome, described previously by our research group, pointed some noncoding RNA (ncRNA) as participants in the restoration of hair-root phenotype in A. thaliana rhd6 mutants, leading us to a deeper investigation. A transcriptional gene expression profiling of seedling roots was performed aiming to identify ncRNA responsive to nitric oxide (GSNO) and auxin (IAA), and their involvement in root hair formation in the rhd6 null mutant. We identified 3,631 ncRNAs, including new ones, in A. thaliana and differential expression (DE) analysis between the following: 1) GSNO-treated rhd6 vs. untreated rhd6, 2) IAA-treated rhd6 vs. untreated rhd6, 3) GSNO-treated rhd6 vs. IAA-treated rhd6, and 4) WS-2 vs. untreated rhd6 detected the greatest number of DE genes in GSNO-treated rhd6. We detected hundreds of in silico interactions among ncRNA and protein-coding genes (PCGs), highlighting MIR5658 and MIR171 precursors highly upregulated in GSNO-treated rhd6 and wild type, respectively. Those ncRNA interact with many DE PCGs involved in hormone signaling, cell wall development, transcription factors, and root hair formation, becoming candidate genes in cell wall modulation and restoration of root hair phenotype by GSNO treatment. Our data shed light on how GSNO modulates ncRNA and their PCG targets in A. thaliana root hair formation.